2015
DOI: 10.3109/02770903.2015.1081699
|View full text |Cite
|
Sign up to set email alerts
|

Impulse oscillometry in acute and stable asthmatic children: a comparison with spirometry

Abstract: IOS has shown a highly significant association with spirometric indices and reversibility testing. It may be a substitute for spirometry in children who fail to perform forced expiratory maneuvers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 24 publications
2
38
0
3
Order By: Relevance
“…Low frequency resistance R5 was selected since it is thought to reflect the caliber of PAW and is commonly used to define a positive BDR. Six pediatric (34-36; 66-68) studies, and 1 adult (30) study reporting the mean and standard deviation (SD) BDR, were analyzed. The 95% upper limit (95% CI) was calculated from the mean + 1.96 residual SD.…”
Section: Assessing Airway Reactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Low frequency resistance R5 was selected since it is thought to reflect the caliber of PAW and is commonly used to define a positive BDR. Six pediatric (34-36; 66-68) studies, and 1 adult (30) study reporting the mean and standard deviation (SD) BDR, were analyzed. The 95% upper limit (95% CI) was calculated from the mean + 1.96 residual SD.…”
Section: Assessing Airway Reactivitymentioning
confidence: 99%
“…In studies utilizing both IOS and spirometry, IOS has been shown to be more useful than spirometry in children in differentiating asthma from normal cohorts, particularly utilizing the BDR decrease in R5 or R10 of 20% in preschool children, (77, 78) and 8.6% in school age children (66) . IOS also proved more diagnostic in identifying uncontrolled asthmatic patients utilizing baseline values (25, 36) . These studies suggest that in children IOS detection of PAI may be more reflective of an earlier event than central airway pathology in asthma identified by spirometry.…”
Section: The Clinical Value Of Iosmentioning
confidence: 99%
“…Impedance outcomes have previously been compared using ROC analysis in children with asthma by Shi et al Here, in correspondence with our results, Fres was shown to have a high AUC at baseline prior to bronchodilator use, though AX and resistance were found to be better outcomes at detecting controlled vs uncontrolled asthma. Similar results using impulse oscillometry were observed by Batmaz et al, who showed both AX and Fres could identify controlled versus uncontrolled asthma and differentiate both forms from healthy controls . While asthma control was not analyzed in our study, it must be noted that all participants in the asthma group were being treated with inhaled corticosteroids to manage their symptoms, which may have dampened the differences from the control group.…”
Section: Discussionmentioning
confidence: 69%
“…Similarly, the impact of salmeterol on baseline lung function can not be excluded despite being withheld on the day of measurement. However, Fres has been shown to be altered in both controlled and uncontrolled asthma, with differences from healthy controls greater in uncontrolled asthma . Finally, although we only examined the ability of FOT outcomes to identify asthma from healthy controls, others have suggested that Fres may be able to predict a 10% change in FEV1, further supporting the suggestion of Fres displaying strong clinical relevance in young children with asthma.…”
Section: Discussionmentioning
confidence: 69%
“…Unlike spirometry, FOT does not require active cooperation or forced respiratory maneuvers and is thus more suitable for young children. FOT has been shown to be more sensitive than spirometry in identifying disturbances of peripheral airway function and has been successfully used for the assessment of pulmonary function in children who cannot perform spirometry during asthma attacks [7][8][9]. However, various factors, including age, sex, height, and weight, are known to influence FOT parameters [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%